Baclofen Response in Alcohol Dependent Patients Concurrently Receiving Antidepressants: Secondary Analysis From the BacALD Study - Heng, Sovandara; Jamshidi, Nazila; Baillie, Andrew; Louie, Eva; Dore, Glenys; Phung, Nghi; Haber, Paul S.; Morley, Kirsten C. (Frontiers in Psychiatry, 2018)
Background and Aims: There is little information with regards to the efficacy of baclofen among alcohol patients concurrently receiving antidepressants (AD). The present study aimed to conduct a secondary analysis of the moderating role of antidepressants in the BacALD trial which evaluated the efficacy of baclofen to reduce alcohol consumption in alcohol dependent patients. Methods: Alcohol dependent patients (N = 104) were treated for 12 weeks with 30 mg/day of baclofen (21 = AD and 15 = no AD), 75 mg baclofen (19 = AD and 16 = no AD) or placebo (17 = AD and 16 = no AD). Patients were included in the trial if they were concurrently receiving anti-depressants upon enrolment but were excluded if they commenced antidepressants two months prior to enrolment. Patients were also excluded in the case of concurrent psychotropic medications, active major mental disorder such as bipolar disorder, psychosis or history of suicide attempt. Predefined primary outcomes included time to lapse (any drinking), relapse (> 5 drinks per day in men and > 4 in women). Other outcomes included drinks per drinking day, number of heavy drinking days, and percentage days abstinent and frequency of adverse events. Results: For the number of days to first lapse, there was a trend of significance for the interaction baclofen x AD (Log Rank: 2= 2.98, P =0.08, OR: 0.41, 95%CI:0.15-1.12). For the number of days to relapse, there was a trend of significant for the interaction of baclofen x AD (Log Rank: 2= 3.72, P = 0.05, OR: 3.40, 95%CI:1.01-11.46). Placing significant baseline variables into the models as covariates (tobacco, ALD) weakened these interactions (P’s > 0.15). There were no significant effects of ADs on the frequency of adverse events reported (P’s > 0.19). Conclusion: Concurrent receipt of ADs commenced more than two months prior to baclofen treatment did not negatively impact on drinking outcomes. Future research examining the interaction between commencing ADs during baclofen treatment on alcohol dependent patients is required. Trial registration: ClinicalTrials.gov, NCT01711125, https://clinicaltrials.gov/ct2/show/ NCT01711125